Analysis of Erosion Management Based on GeoWEPP Spatial Modeling on Bauxite Mining Activities PT. XYZ in West Borneo - Santoso, Rika Setiabudi; Mulatsih, Sri; Setiawan, Yudi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Bauxite ore open-pit mining activities are conducted in spread areas and increase the potential for water pollution, implying a need for good management. GeoWEPP is a spatial model that predicts the erosion magnitude and the location of sedimentation. This helps in erosion management and control, including constructing a settling pond. Therefore, the purpose of this study was to examine GeoWEPP based on land use, topographic and soil maps, as well as rainfall and temperature data. The results showed that 30 hills with a total area of 13 602.48 Ha obtained sediment of 150 186 m3/month and the amount of run off of 4 202 267 m3/month. Furthermore, GeoWEPP analysis on the planned mining block area obtained 30 outlet points to be used as the location for the settling pond construction. The optimistic and pessimistic cost of constructing the entire settling pond is Rp. 222 047 640 944 and Rp. 222 773 049 768, respectively. Additionally, the cost of settling pond maintenance at all outlet points during operation is Rp. 3 139 414 818. Planting cover crops in ex-mining areas is very effective in reducing erosion.